H Syndrome: A case report and review of literature - Dilip Meena; Payal Chauhan; Neirita Hazarika; Naveen Kumar Kansal (Wolters Kluwer Medknow Publications, 2018)
H syndrome is a rare autosomal recessive syndrome characterised by constellation of clinical features and systemic manifestations including cutaneous hyperpigmentation, hypertrichosis, hepatosplenomegaly, hearing loss, heart anomalies, hypogonadism, hyperglycaemia, low height, and hallux valgus. We report a case of this syndrome with typical clinical findings. We report this case citing the rarity of this uncommon entity.